Different Shades—Different Effects? Consequences of Different Types of Destructive Leadership - Schmid, Ellen A.; Pircher Verdorfer, Armin; Peus, Claudia V. (Frontiers in Psychology, 2018)
Destructive leadership comes in many shapes and forms. From reviewing the literature, we conclude that three major forms of destructive leader behaviors are described: 1) follower-directed destructive behaviors, i.e., genuine abusive forms of destructive leadership, 2) organization-directed behaviors, i.e., behaviors such as stealing from the organization or embezzlement, and 3) self-interested destructive leader behavior, i.e. leader who exploit others to reach their goals. One can easily imagine that these three types of leader behavior have very different effects on followers. Unfortunately, so far, there is no empirical evidence to support this, since comparative research in the field of destructive leadership is scarce. With this paper, we aim to address this gap: In two studies, an experimental and a field study, we examine the differential impact of these three different destructive leader behaviors on two important outcomes: first, their impact on different emotional reactions of followers, the most proximal outcome to a social interaction. Second, we examine a key outcome in leadership research: followers’ turnover intention. The results suggest that different types of destructive leader behavior do impact followers differently. Whereas all three behaviors had a positive relationship with negative affect, follower-directed destructive behaviors had the strongest relation out of the three. As expected, all three types of destructive behavior relate to turnover intention, yet, the results of our study suggest that different types of destructive leader behavior relate to different urgencies of turnover intention. We conclude that a tailored approach to destructive leadership, whether in research or practice, seems necessary, as diverse types of destructive leader behaviors affect employees differentially.